International Protection of Cultural Heritage in Armed Conflict: Revisiting the Role of Safe Havens - Jakubowski, Andrzej (UI Scholars Hub, 2019)
In 2017, the UN Security Council adopted Resolution 2347, lauded as “a historic milestone” in the international struggle to safeguard cultural heritage in armed conflict. Among a wide spectrum of recommended actions, this instrument encourages the UN State Members to establish a network of “safe havens” in their own territories to protect cultural property, “while taking into account the cultural, geographic, and historic specificities of the cultural heritage in need of protection.” In this regard, Resolution 2347 makes explicit reference to the 2016 Abu Dhabi Declaration on heritage at risk in the context of armed conflicts, a Declaration which promotes the creation of a network of “safe havens” in the country of origin, and as a last resort in another country. This article discusses the international law framework of extraterritorial “safe havens” for cultural property. In particular, it analyses: 1) the legal notion of safe haven in international law documents; 2) the operationalisation of safe havens for endangered cultural property in the practice of states, analysing recent regulatory initiatives at the national level; and 3) safe havens in the global, multi-faceted governance of cultural heritage, examining the relevance of safe havens for peacekeeping operations and for the development of the UN doctrine of Responsibility to Protect.